PENGARUH KOMPETENSI DISIPLIN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PERUSAHAAN KARGO DI KOTA BATAM - Wasiman (Postgraduate Management Journal, 2022)
This study aims to see the effect of competence, discipline and motivation on the performance of cargo company employees in Batam City. This study uses a questionnaire distributed to employees of cargo companies in Batam City with a questionnaire of 113 respondents. This research uses individual level analysis. The object of research is the employee of the cargo company Batam City. This study uses multiple linear regression test which includes validity, reliability, normality, and r-square tests. The results showed that the results of the validity test showed that all indicators showed validity results that could lead to the next stage, and also the reliability results concluded that all the data collected and reliable. The coefficient of determination (R2) is 0.870, which means that the performance variable can be explained by the competence, discipline and motivation variables of 87%, while the remaining 13%. % is another factor outside the variables studied